IMPACT OF INFLATION UNCERTAINTY ON THE FINANCIAL STRUCTURE OF MUNICIPALITY AND URBAN MANAGEMENT - Azimi, Mitra; Pendar, Mahdi (ВЕСТНИК ЧЕЛЯБИНСКОГО ГОСУДАРСТВЕННОГО УНИВЕРСИТЕТА; № 2(436) (2020): Вестник Челябинского государственного университета, 2022)
One of the most important problems which politicians and urban managers are always involved in is the limited resources to meet the needs of city and citizens. Hence, it can be seen that the strategy of financing the country’s municipalities is mainly focused on more revenue, most of which are unstable and unjust and little by little has pushed their revenue structure towards inconstancy. Therefore, making a reform on how to finance municipalities has become an essential matter in urban managers’ programs to find ways to fix it, while they try to identify the causes of instability. One of the factors affecting the stability of municipalities’ revenue structure is the inflation uncertainty. Hence, in this paper, using descriptive and analytical methods and library study, the researchers first extracted the theoretical concepts and principles regarding inflation uncertainty. Then, to find the inflation rate, they used general autoregressive variance anisotropy method so that they could study the existence of this factor in the structure of municipal revenue (for example: Tehran Municipality) in a time interval of 2001–2013 and its effects on the stability of revenue system. In the following, in order to make clear the impacts of inflation uncertainty on the urban management, the researcher took advantage of constitutional view on a costs economic theoretical framework. Findings indicate that in the time interval of the above-stated years, inflation uncertainty has played an important role in the inconsistency of Tehran Municipality structure. Furthermore, this factor, along with increasing the transactional cost has caused the urban management body to finally face (by creating disorders in compiling and administering the programs, tendency to make short and mid- programs, the lack of interest in private firms in making cooperation with the municipality, increasing the risk of municipal economic activities) mistrust atmosphere among the citizens.   DOI:   https://doi.org/10.24411/1994-2796-2020-10207